A new approach to use Arenga pinnata as sustainable biopolymer: effects of plasticizers on physical properties - Sahari, J.; Sapuan, S. M.; Zainudin, E.S.; Maleque, Md. Abdul (Elsevier, 2012)
The motivation of this research is to develop a new biopolymer derived from sugar palm tree (Arenga pinnata) which can lead to solve non degradable polymer waste disposal problems. Therefore, this paper presents the development of alternative biodegradable material developed by using locally available sugar palm starch (SPS) in presence of biodegradable glycerol as a plasticizer. The environmental friendly plasticized SPS were successfully prepared using 15, 20, 30 and 40% w/w of glycerol. The samples were characterized for density, moisture content, water absorption and thickness swelling. The results showed that the physical properties i.e. density, moisture content, water absorption and thickness swelling of the plasticized SPS become lower with the increasing of glycerol content.